Mengamati Sinyal R Gelombang QRS Jantung Dengan Interpolasi Linier - Pramuyanti, Roni Kartika (ReTII, 2023)
R signal QRS wave is the Amplitudo of PQRST heart signal. Where thereis R signal the heart signal is the periodic signal which there is untull the human is mot death. In medics word the out of signal is an error of the human or the humN IS SICK. In tectique word the heart signal can be gotten the equation og R signal. In tecnics thereis Interpolation equations. In This Interpolation we must know some dot of the signal, in this case about R signal the Linier Interpolation is so . Thereare two equation linier Interpolation. In this case there is norm heart signal and we can get this equation is : Y1 = 50x + 225 and Y2 = -20x + 9,6. Keyword : Amplitudo, Periodic, Interpolation, Linier Interpolation